Candidate gene SNP variation in floodplain populations of pedunculate oak (Quercus robur L.) near the species' southern range margin: Weak differentiation yet distinct associations with water availability. Issue 13 (21st June 2020) - Temunović, Martina; Garnier‐Géré, Pauline; Morić, Maja; Franjić, Jozo; Ivanković, Mladen; Bogdan, Saša; Hampe, Arndt
Abstract: Populations residing near species' low‐latitude range margins (LLMs) often occur in warmer and drier environments than those in the core range. Thus, their genetic composition could be shaped by climatic drivers that differ from those occurring at higher latitudes, resulting in potentially adaptive variants of conservation value. Such variants could facilitate the adaptation of populations from other portions of the geographical range to similar future conditions anticipated under ongoing climate change. However, very few studies have assessed standing genetic variation at potentially adaptive loci in natural LLM populations. We investigated standing genetic variation at single nucleotide polymorphisms (SNPs) located within 117 candidate genes and its links to putative climatic selection pressures across 19 pedunculate oak ( Quercus robur L.) populations distributed along a regional climatic gradient near the species' southern range margin in southeastern Europe. These populations are restricted to floodplain forests along large lowland rivers, whose hydric regime is undergoing significant shifts under modern rapid climate change. The populations showed very weak geographical structure, suggesting extensive genetic connectivity and gene flow or shared ancestry. We identified eight (6.2%) positive F ST ‐outlier loci, and genotype–environment association analyses revealed consistent associations between SNP allele frequencies and several climatic variables linked to water availability. A total of 61 associations involving 37 SNPs (28.5%) from 35 annotated genes provided important insights into putative functional mechanisms in our system. Our findings provide empirical support for the role of LLM populations as sources of potentially adaptive variation that could enhance species' resilience to climate change‐related pressures.